2022
DOI: 10.1002/aesr.202200134
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Solar Energy for Cathodic Protection of Metals: The Life of Photoexcited Charge Carriers

Abstract: Figure 7. a) Schematic illustration, SEM image and OCP test results of a TiO 2-BiVO 4 -CdS heterojunction photoanode. Reproduced with permission. [36] Copyright 2022, Elsevier; b) Schematic illustration, SEM image and OCP test results of a COF(TpBD)-TiO 2 photoanode. Reproduced with permission. [33] Copyright 2020, Elsevier; c) Schematic illustration, SEM image and OCP test results of a SnO 2 /TiO 2 nanorods photoanode. Reproduced with permission. [37] Copyright 2020, Elsevier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 139 publications
0
4
0
Order By: Relevance
“…The photogenerated electrons of the coating could migrate to the metal substrate, resulting in its cathodic polarization so-called photocathodic protection. 5,6 It is energy saving and could supply long-term corrosion protection. 7 Recently, researchers have revealed that TiO 2 , 8−10 Cu 2 O, 11 and g-C 3 N 4 12,13 are suitable for photocathodic protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photogenerated electrons of the coating could migrate to the metal substrate, resulting in its cathodic polarization so-called photocathodic protection. 5,6 It is energy saving and could supply long-term corrosion protection. 7 Recently, researchers have revealed that TiO 2 , 8−10 Cu 2 O, 11 and g-C 3 N 4 12,13 are suitable for photocathodic protection.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this essence, the application of semiconductor coatings on the steel surface could be an effective method for corrosion prevention, which generates charges under illumination. The photogenerated electrons of the coating could migrate to the metal substrate, resulting in its cathodic polarization so-called photocathodic protection. , It is energy saving and could supply long-term corrosion protection . Recently, researchers have revealed that TiO 2 , Cu 2 O, and g-C 3 N 4 , are suitable for photocathodic protection.…”
Section: Introductionmentioning
confidence: 99%
“…In the conventional PECCP systems, the water oxidation process (oxygen evolution reaction, OER) at the semiconductor-electrolyte interface involves the complex formation of four-electron O-O bonds, resulting in substantial reaction overpotentials (Z) and sluggish kinetics. [9][10][11][12] Among the semiconductors used in PECCP systems, one-dimensional n-type TiO 2 nanostructures, such as nanorods, have received the most attention because of their enhanced charge transport along their longitudinal direction, light-trapping characteristics, and large specific surface area. [13][14][15][16] However, TiO 2 has a high OER reaction energy barrier and possesses limited surface active sites.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Under the influence of external forces, such as an electric field, e – and h + may move in different directions. (3) e – migrates to the protected metal and provides CP to metals. , PCP coating technology combines the advantages of coatings and CP; this coating acts as a photoanode and converts solar energy into electricity through photoelectrochemical reactions . From the service process of the PCP coatings, it can be found that the PCP process only consumes solar energy and does not produce harmful products.…”
Section: Introductionmentioning
confidence: 99%